IMPLEMENTASI E-SAMSAT PADA PEMBAYARAN PAJAK KENDARAAN BERMOTOR OLEH WAJIB PAJAK DI KOTA BEKASI - Thio, Luky (Jurnal Nusa Akuntansi, 2024)
The research objective of this thesis aims to analyze the influence of e-invoicing, tax understanding, tax sanctions on taxpayer compliance on social media at the Pasar Minggu tax office. The sample in this research is corporate taxpayers. The number of samples taken in this research was 2,315 personal taxpayers reporting on the KPP Pratama Pasar Minggu social media. In carrying out data collection, this was done by distributing a questionnaire in which there were several statement items. In this research, the variables are divided into several parts, including e-invoicing (X1), understanding of taxes (X2) and tax sanctions (X3) as independent variables, and taxpayer compliance (Y) as the dependent variable. To measure the magnitude of the influence on these variables, the author uses the multiple regression method. From the results of this analysis, it was found that there is a significant and simultaneous influence on the variables e-invoicing (X1), tax understanding (X2) and tax sanctions (X3) on taxpayer compliance (Y).